Optimalisasi Pendampingan Kegiatan Malam Bina Iman Dan Taqwa (Mabit) Dalam Meningkatkan Kecerdasan Spiritual Santri Madrasah Diniyah Al- Mutmainnah Winong Jetis Ponorogo - Umro'atin, Yuli; Salim, Muhamad Nur (Community Development: Jurnal Pengembangan Masyarakat Islam, 2025)
Optimizing The Faith And Devotional Night Guidance (Mabit) Activity To Improve The Spiritual Intelligence Of Students At Al-Mutmainnah Diniyah Madrasah Winong Jetis Ponorogo. Spiritual intelligence is very important for every human soul, although brain intelligence (IQ) cannot be denied. Many people have intellectual intelligence, but fail in living their lives and social activities. They have personalities that do not integrate between reason and heart. This guidance process prioritizes the balance of life in the world and the hereafter, through the practice of sharia. This community service activity aims to improve the spiritual intelligence of students at Al-Mutmainnah Islamic school Winong Jetis Ponorogo through the activity of fostering faith and piety nights, and analyzing the success of the mentoring process in the activity of fostering faith and piety nights towards improving the spiritual intelligence of students at Al-Mutmainnah Islamic school Winong Jetis Ponorogo. This service uses the PAR or Participatory Action Research method. PAR is a research process that involves human resources (HR), especially researchers and devotees, which aims to solve problems. Results: The process of implementing the mentoring of the night of faith and piety activities at the Al-Mutmainnah Islamic school includes several stages. First, it begins with preparing a plan that includes activities to formulate objectives, socialize the program plan, determine schedule of activities and tasks of the mentors, and determine indicators of activity achievement. Second, the stage of implementing activities in the form of coaching, training, monitoring, increasing spirituality through Islamic tausiyah/storytelling, getting used to obligatory and sunnah worship, and others. The last stage is evaluation and continuous improvement.